1984
DOI: 10.1139/m84-162
|View full text |Cite
|
Sign up to set email alerts
|

Experimental meningococcal infection in neonatal mice: differences in virulence between strains isolated from human cases and carriers

Abstract: The lack of availability of a suitable animal model has limited understanding of the pathophysiology of meningococcal disease. We have utilized a neonatal mouse model in which atraumatic intranasal inoculation of meningococci results in nasopharyngeal colonization and ultimately bacteremia. Using this model, we compared the virulence of seven encapsulated meningococcal carrier strains with eight meningococcal strains which were isolated from cerebrospinal fluid or blood of patients (disease strains). Intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies by several authors [25,26] showed a clear relationship between growth in iron-restricted conditions and virulence in N. meningitidis strains and, as proteins which axe expressed under such conditions have been implicated as functional components of the iron-uptake systems of a number of bacteria [3], it can be expected that also in IV, meningitidis they are involved in these virulence processes.…”
Section: Meningitidismentioning
confidence: 99%
“…Studies by several authors [25,26] showed a clear relationship between growth in iron-restricted conditions and virulence in N. meningitidis strains and, as proteins which axe expressed under such conditions have been implicated as functional components of the iron-uptake systems of a number of bacteria [3], it can be expected that also in IV, meningitidis they are involved in these virulence processes.…”
Section: Meningitidismentioning
confidence: 99%
“…i.n. models have mainly used neonatal mice (28,38) to analyze disease pathogenesis and virulence of meningococcal isolates (29,37). Interestingly, meningococcemia was also induced by the i.n.…”
mentioning
confidence: 99%
“…We have described a neonatal mouse model for meningococcal disease in which the intranasal inoculation of bacteria is followed by a phase of nasopharyngeal colonization (25,26). Virulent and avirulent strains attach to and colonize the murine nasopharynx to the same degree, but it is mainly those strains which are virulent for humans which invade through the nasal mucosa and cause bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Strains of N. meningitidis isolated from blood or spinal fluid were designated "case strains," whereas those derived from the pharynxes of asymptomatic persons were designated "carrier strains." The strains which were used in this study and previous studies (25,26) were characterized as to capsular serogroup and serotype (serogroup/serotype). Disease-associated strains were B16B6 (B/2a), M986 (B/2a,7), 3006 (B/2b), BB80 (B/2), M1011 (B/2,10), BB106 (C/2), BB138 (C/2), BB155 (C/2), and VM63 (nongroupable).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation